CORRELATION BETWEEN SLEEP APNEA AND METHADONE THERAPY - Christiana Madjova; Simeon Chokanov; Mario Milkov (Peytchinski Publishing, 2021)
Introduction: Methadone therapy is the mainstay of treatment of addict patients. The most common side effects are: dizziness, drowsiness, vomiting, sweating, dry mouth and constipation. The more serious complications that can be observed are: sleep apnea, аbnormal heart rhythms, respiratory problems, euphoria, disorientation, anxiety, seizures and more. Purpose: The purpose of this study is to determine the correlation between methadone maintenance treatment and sleep apnea in addict patients. Materials and methods: The subject of the study are 81 methadone-treated drug-dependent patients, mean age 39 ± 9,07 years. Results: The answers we received: 79% (64) of drug addicts have problems with sleep; 30.9% of them (25) reported having insomnia; 44.4% (36) experience morning fatigue; 56.8% (46) of the respondents said they were drowsy during the day and 63% of the respondents reported a change in mood; 21% (17) had a short sleep, and 26% (21)reported snoring and 18 of them have loud bothering snoring; 68% answered that they don't have problems with falling asleep and only 21% don't wake up frequently in the evening. In 83.9% nobody noticed cessation of breathing during sleep. 73.8% never nodded off or fallen asleep while driving a vehicle. 16.1% have been treated for high blood preasure, and only 2.5% have obesity. Conclusions: Our survey found that there is a correlation between methadone therapy and sleep of patients. The key to improving the condition and reducing the risk of central sleep apnea is the monitoring of patients, as well as a combination of different types of treatment.